Lexical Semantic Review of Alpha Generation Terms; Previous Generation’s Perspective - Amelia Ayu Putri Nabilah; Dimas Adika (CV. Tirta Pustaka Press, 2025)
Our perception and analysis delve into the evolving linguistic landscape of Generation Alpha, a generation deeply intertwined with digital technology, by orienting to their language use often missed by their guardian. This paper intends to examine how language understanding impacts and may bring a new perspective. To discover the spot, this study utilized a convergent parallel mixed-methods design. A questionnaire survey of 130 respondents was conducted and randomly assigned among internet users through social media in aims to determine the population’s attentive and digital language use preferences. The result we found was digital communication has become challenging that more than half of respondents derived from Generation Z in several countries, along with the semantics analysis of common slang that Alpha Generation frequently used such as Sigma, Mewing, Skibidi, Delulu, and Rizz which were chosen by respondents especially are familiar for Alpha Generation’s educators and parents. Linguistics holds immense potential but faces significant challenges. Our research is of great significance to digital culture, especially teachers and parents. By inclined to present the understanding of language development anticipated to be a starting point to provide valuable insight into digital communication that may help young generation protectors to able to take precise steps.